Assessment of surface runoff conditioned by road works and urban settlements in large plain basins - Borzi, Guido Esteban (2020)
The province of Buenos Aires located in Argentina contains numerous agricultural plain basins of world importance among which the Samborombon river basin stands out, where regular floods affect agricultural activities and urban expansion. This sector has large road works with approach embankments that obstruct the natural drainage, a poorly planned urban growth, and an increase in the rainfall regime in recent decades. The aim of this work is to carry out an analysis and assessment of the surface runoff conditioned by road works and urban settlements in large plain basins, taking the Samborombon river basin as a case study. Satellite images were used to define the floodplain and identify the main road works and urban settlements that develop within it. Subsequently, hydrological simulations were carried out to assess how these anthropic structures modify the surface runoff and the flooded areas. To validate the simulation results, the flooded areas obtained were compared with a similar flood event of a Landsat image. The results show that the road works embankments and urban settlements restrict the floodplain area of the river, generating an increase in the flooded area and delaying the water runoff. This problem, together with the rainfall increase, shows the need to generate a territorial management plan and adopt mitigation measures. The use of sacrificial embankments could be an economic alternative that would prevent the obstruction of water runoff, being able to use the basin as a pilot site for this innovative idea.